Positive deviance inquiry of breastfeeding in Egypt - Sarhan, Ayah (AUC Knowledge Fountain, 2020)
Increases in malnutrition among Egyptian children under five years have been associated with decreases in rates of breastfeeding. International and national research have identified personal and contextual challenges that lower the chances of women breastfeeding. These challenges include lack of knowledge and support by medical personnel and family, negative societal attitudes, and institutional practices that inhibit breastfeeding. In this study, a positive deviance approach was used to identify the practices that enabled middle-class Egyptian women to initiate and continue breastfeeding. Data was collected from 33 positive deviant mothers using a survey and a semi-structured interview. Findings confirmed that they faced personal and structural challenges and including cultural beliefs and practices. Positive deviant mothers' persistence, self-efficacy, and confidence were enabling personal factors. They were aware of breastfeeding benefits to the baby. In addition, they insisted that their needs be met, ignored disempowering advice and people, and were eager to learn. Based on these findings, it is recommended to design a community intervention program for pregnant mothers to strengthen self-efficacy and inform them how to start and continue breastfeeding, and communicate and elicit help from their significant family members. Also, mothers need access for support from medical practitioners trained in lactation management and to network with other mothers in support groups. Other structural factors require policy change to allow for flexible work arrangements, or facilities that would enable them to continue breastfeeding.